Legal Framework for Russian Federation Leaving the Jurisdiction of the European Court of Human Rights - P. Yu. Ulturgashev (Теоретическая и прикладная юриспруденция)
Article aims to compare the legal framework for ceasing of a state’s membership in the Council of Europe and Convention for the protection of Human Rights and Fundamental freedoms with the factual application of relevant framework in respect of the Russian Federation leaving the CoE in 2022. Analysis shows that foreseen procedures were o complied with, leading to defect actions and decision on the part of European party, and to somewhat inconsistent legal framework adopted in Russia. Lack of dialogue between the parties resulted in creation of two virtually unconnected legal realities. While the Council of Europe bodies and the Russian authorities apparently do not experience substantial adverse effects of this situation, the burden of such consequences is placed on the applicants, particularly on Russian citizens. It is assumed that very limited opportunities remain for interaction between Russian and European legal systems in terms of ensuring the rights of citizens.